Constructing of Some New Results in Intuitionistic Fuzzy Metric Space by Applying the Abstraction of Fuzzy Iterated Contraction - SEWANI, GODAVARI; SINGH, A.D.; SINGH, RUCHI; BHARDWAJ, RAMAKANT (The journal of contemporary issues in business and government, 2021)
Fixed point results are established at the basis of Banach contraction principle. Many authors extended this result in different form for different type of mappings in various ways according to their applications. The extension can be useful for uncertainty theory obtained by fuzzy sets and soft sets. In this paper, we establish a couple of fixed-point results for fuzzy iterated contraction in the intuitionistic fuzzy metric space. Obtained results are generalization form of well-known results . The established results can further be generalized for soft sets as fixed point theorems for fuzzy soft sets or soft fuzzy sets. The couple fixed point theorems will be useful in the management study as well as in stock marketing.